Mobile Platform Preference: A Comparison of U.S., Indian and Japanese Firms - Janice A. Hauge; Mark A. Jamison; Jakub Tecza (American Enterprise Institute (AEI), 2023)
We examine businesses' choices of mobile platforms – iOS and Android – contrasting firms in the U.S., India, and Japan. Using Crunchbase® data on startups seeking external funding, we find that many of the 47 business categories analyzed are likely to use mobile platforms, but some have a negative propensity to do so. Many that tend to use platforms exhibit no platform preferences, implying substitutability. Many that do exhibit a platform preference also tend to not use platforms, indicating an indifference as well. Results across India, Japan, and the U.S. are largely similar, with the exception of more business categories exhibiting platform preferences in the U.S.
Keywords: 330; platforms; network effects; competition; differentiation; startups